Communication channels in the host community market adopted by Chinese immigrant entrepreneurs - Tinashe T.R. Ndoro; Lynette Louw; MacDonald Kanyangale (Acta Commercii, 2018)
Orientation: There is a growing prevalence of entrepreneurial activity by immigrant entrepreneurs in different sectors of various economies across the world. Immigrant entrepreneurs seek to identify opportunities to grow and sustain their businesses in hostile business markets. Immigrant entrepreneurs use an array of channels of communication to gain insight of the opportunities in the market.